PERAN UNIT TURJAWALI SATUAN LALU LINTAS POLRES BOGOR DALAM MENGURAI KEMACETAN DI JALUR PUNCAK - Arsyad Daiva Gunawan (Advances in Police Science Research Journal, 2020)
This research is in the background because it stays in the existing traffic jam at Puncak from the Bogor Police Traffic Turjawali Unit to prevent traffic congestion. with the existence of distancing by guarding the point prone to congestion, but this has not shown the expected results. Therefore, a study was carried out aimed at summarizing the congestion that occurred at the Peak, the efforts undertaken by the Bogor Police Traffic Unit Turjawali Unit in unraveling congestion in the Peak Lane, and what factors were used by the Turjawali Unit to unravel traffic jams . This study, using qualitative research, took data from interviews, observations, and documentation studies. The results of the study were found after being analyzed using the concept of struggle and the Standard Operating Procedure (SOP) efforts made by the Bogor Police Traffic Turjawali Unit were appropriate, discussed analyzed with management theory for technical organizing, still far from expectations due to support from the Turjawali Unit. Analyzing using the theory of traffic congestion also found that the obstacle was in human resources, namely the ability of the Turjawali Unit because it had not yet supported competency development education. Based on the results of the study, the author discusses the need to improve the quality of the members of the Turjawali Unit by including the members of the turjawali unit for the implementation of development education in accordance with their duties, after that form a task force that is enhanced with the help of institutions, such as the transportation service and the service. hope to achieve the highest level in the Peak Track. Keywords: traffic jam, Peak Lane, Turjawali, Kamseltibcar, standard operational procedures.